Geochemical Characteristics and Environmental Risks of Cu in the Soil of A Sloping Vineyard (Phu Tho Province, Vietnam) - Thi Ha Nhung, Pham; Quoc Viet, Nguyen; Thi Thanh Huong, Tran; Thi Nga, Dang; Thanh Vinh, Nguyen; Viet Truong, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1S, 2024)
In the vineyards, the intensive use of cupric fungicides and fertilizers has resulted in Cu enrichment in the soils. Specifically, in sloping vineyards, the mobility of Cu can contribute to intensify the environmental risks. The research on geochemical characteristics of Cu is a key solution to explore the distribution of Cu in different geochemical fractions and understand the mobility and toxicity of this element in the environment. In this study, we aim to investigate the geochemical properties of Cu in the vineyard topsoil (0-20 cm) and subsoil (20-40-60 cm), using the improved three-step sequential extraction procedure developed by the Commission of the European Communities Bureau of Reference (BCR). In addition, the environmental risk is calculated by the environmental risk code (RAC) based on the percentage of Cu in the acid-soluble fraction. The results reveal that the mobility of Cu in the acid-soluble fraction (F1) and reducible fraction (Cu associated with the iron and manganese oxyhydroxides) (F2) tends to decrease with increasing soil depth. The major portion of Cu mostly exists in the strong bond with silicate clays (F4), accounting for 84% of total Cu content on average. Contrarily, the minor propotion of Cu associates with soil organic matter (F3) (3% on average). On the other hand, the content and proportion of Cu in the soil fractions are largerly influenced by basic soil properties (organic matter contents and fine soil particles). In addition, under the impact of soil erosion, higher percentages of F1 and F2 fractions of Cu are observed in the surface soil layers at the top of the hill compared to those at the backslope of the hill. The mean calculated RAC of 10.66%, 5.76%, and 5.38% for the 0-20 cm, 20-40 cm, and 40-60 cm soil layers, respectively, demonstrate a low risk to medium environmental risk level in the studied vineyard. Although an overall low risk level is observed for Cu in the studied vineyard soil, the deposition of Cu originating from repeated Cu-based pesticides and erosion is of particular concern in the vineyard soils.